Family Mediation and Arbitration Practises in Saudi Arabia - Fulya Okur (Darulfunun Ilahiyat)
Sociological and administrative issues arising from family disputes and increasing divorce rates have been among the significant problems of the 20th century. Family mediation, one of the methods used to address these issues, has gained importance as a solution shaped by different cultures and beliefs. In Türkiye, there are plans to implement mediation as an alternative dispute resolution method, with a prevailing understanding that European-originated methods could be employed in this process. However, considering the cultural differences between Europe and Türkiye, there is also a tendency towards developing a model that aligns with Türkiye’s cultural structure, which is believed to yield more positive and beneficial outcomes for Turkish society. Indeed, various academic studies are being conducted to pave the way for the creation of a unique system developed by benefiting from the experiences of countries that have recently implemented such practises. This study examines the family mediation and arbitration practises of the Kingdom of Saudi Arabia, which bases its applicable family law on Islamic law and maintains an established Islamic cultural framework in its social life, with the aim of contributing to existing research.